Protein accumulation and rumen stability of wheat γ‐gliadin fusion proteins in tobacco and alfalfa. Issue 7 (6th February 2015) - Sun, Xiaodong; Chi‐Ham, Cecilia L.; Cohen‐Davidyan, Tamar; DeBen, Christopher; Getachow, Girma; DePeters, Edward; Putnam, Daniel; Bennett, Alan
Summary The nutritional value of various crops can be improved by engineering plants to produce high levels of proteins. For example, because methionine deficiency limits the protein quality of Medicago Sativa (alfalfa) forage, producing alfalfa plants that accumulate high levels of a methionine‐rich protein could increase the nutritional value of that crop. We used three strategies in designing methionine‐rich recombinant proteins that could accumulate to high levels in plants and thereby serve as candidates for improving the protein quality of alfalfa forage. In tobacco, two fusion proteins, γ‐gliadin‐δ‐zein and γ‐δ‐zein, as well as δ‐zein co‐expressed with β‐zein, all formed protein bodies. However, the γ‐gliadin‐δ‐zein fusion protein accumulated to the highest level, representing up to 1.5% of total soluble protein (TSP) in one transformant. In alfalfa, γ‐gliadin‐δ‐zein accumulated to 0.2% of TSP, and in an in vitro rumen digestion assay, γ‐gliadin‐δ‐zein was more resistant to microbial degradation than Rubisco. Additionally, although it did not form protein bodies, a γ‐gliadin‐GFP fusion protein accumulated to much higher levels, 7% of TSP, than a recombinant protein comprised of an ER localization signal fused to GFP in tobacco. Based on our results, we conclude that γ‐gliadin‐δ‐zein is a potential candidate protein to use for enhancing methionine levels in plants and for improving rumen stability of forage protein. γ‐gliadin fusion proteins may provide a general platform for increasing the accumulation of recombinant proteins in transgenic plants.